Blackout - Ragnar Jónasson, 1976- (Ragnar Jónasson, 1976- Dark Iceland series., 2018)
Ari Thor Arason and his colleagues investigate a murder under the shadow of a volcanic ash cloud, while personal problems and a reporter with a secret agenda complicate their work.